Structural performance of ultra-high-performance concrete beams with different steel fibers. (1st November 2015) - Yoo, Doo-Yeol; Yoon, Young-Soo
Highlights: Enhanced load carrying capacity and stiffness are obtained by adding steel fiber. The use of longer fiber and twisted fiber is effective in improving ductility. The inclusion of steel fiber leads to decrease in ductility index. The use of K = 1.25 is proper for predicting flexural response of UHPC beam. Abstract: In this study, ten large ultra-high-performance concrete (UHPC) beams reinforced with steel rebars were fabricated and tested. The experimental parameters included reinforcement ratio and steel fiber type. Two different reinforcement ratios ( ρ = 0.94% and 1.50%) and steel fiber types (smooth and twisted steel fibers) were adopted. In addition, three different fiber lengths ( Lf = 13, 19.5, and 30 mm) for the smooth steel fibers and one fiber length ( Lf = 30 mm) for the twisted steel fiber were considered. For a control specimen, a UHPC matrix without fiber was also considered. Test results indicated that the addition of steel fibers significantly improved the load carrying capacity, post-cracking stiffness, and cracking response, but it decreased the ductility. Specifically, with the inclusion of 2% by volume of steel fibers, approximately 27–54% higher load carrying capacity and 13–73% lower ductility were obtained. In addition, an increase in the length of smooth steel fibers and the use of twisted steel fibers led to the improvements of post-peak response and ductility, whereas no noticeable difference in the load carrying capacity, post-cracking stiffness, and cracking response were obtained according to the fiber length and type. Sectional analysis incorporating the suggested material models was also performed based on AFGC/SETRA recommendations, and the ratios of flexural capacities obtained from experiments and numerical analyses ranged from 0.91 to 1.19.